Defining recurrent pregnancy loss: associated factors and prognosis in couples with two versus three or more pregnancy losses. Issue 4 (October 2020) - Youssef, Angelos; Lashley, Lisa; Dieben, Sandra; Verburg, Harjo; van der Hoorn, Marie-Louise
Abstract: Research question: The definition of recurrent pregnancy loss (RPL) differs internationally. The European Society of Human Reproduction and Embryology (ESHRE) defines RPL as two or more pregnancy losses. Different definitions lead, however, to different approaches to care for couples with RPL. This study aimed to determine whether the distribution of RPL-associated factors was different in couples with two versus three or more pregnancy losses. If a similar distribution were found, couples with two pregnancy losses should be eligible for the same care pathway as couples with three pregnancy losses. Design: This single-centre, retrospective cohort study investigated 383 couples included from 2012 to 2016 at the Leiden University Medical Center RPL clinic. Details on age, body mass index, smoking status, number of pregnancy losses, mean time to pregnancy loss and performed investigations were collected. The prevalence of uterine anomalies, antiphospholipid syndrome, hereditary thrombophilia, hyperhomocysteinaemia, chromosomal abnormalities and positive thyroid peroxidase antibodies were compared in couples with two versus three or more pregnancy losses. Results: No associated factor was found in 71.5% of couples with RPL. This did not differ statistically between couples with two versus three or more pregnancy losses (73.6% versus 70.6%; P  = 0.569). The distribution of investigated causes did not differ between the two groups. Conclusions: As the distribution of associated factors in couples with two versus three or more pregnancy losses is equal, couples with two pregnancy losses should be eligible for the same care pathway as couples with three. This study supports ESHRE's suggestion of including two pregnancy losses in the definition of RPL.